Coaching And Mentoring Models In Increasing The Capacity Of Novice Elementary School Teachers - Demena, Widelmina K.; Padang, Nasri Indra; Lewaherilla, August (PT. Anagata Sembagi Education, 2025)
Beginning elementary school teachers face complex challenges when entering the workforce, particularly in classroom management, curriculum adaptation, and meeting professional expectations. Despite possessing theoretical knowledge from higher education, limited practical experience often undermines self-confidence and potentially hinders the quality of learning. This situation emphasizes the need for systematic professional mentoring to ensure a more effective transition to the workforce. Coaching and mentoring have emerged as relevant strategies capable of bridging the gap between theory and practice. Coaching focuses on reflective empowerment through structured dialogue, while mentoring emphasizes the transfer of professional skills and values from senior teachers to beginning teachers. The integrated application of both creates synergy in strengthening teacher capacity across cognitive, affective, and practical aspects. This literature review examines the effectiveness of coaching and mentoring as models for continuous professional development. The analysis shows that these strategies not only improve instructional skills but also strengthen beginning teachers' professional identity, foster a collaborative culture in schools, and positively impact student learning outcomes. With appropriate policy support, coaching and mentoring can be strategic instruments for improving the quality of elementary education. Therefore, the integration of these two approaches should be viewed as a long-term investment in teacher capacity building and achieving national education goals